THE EFFECT OF JOB TRAINING AND CAREER DEVELOPMENT ON EMPLOYEE PERFORMANCE - Riski Ulan Sari; Rd Roro Anggraini Soemadi (ZILLZELL MEDIA PRIMA, 2024)
The purpose of this study is to determine the influence of Job Training and Career Development on Employee Performance partially and simultaneously in PT Shield on Service Academy Hypro. The research method used is a quantitative method. The sample taken in this study amounted to 50 employees. The analysis method used is multiple regression analysis. Data collection was obtained from the distribution of questionnaires. The results of the study showed that partially the Job Training variable (X1) did not have a positive and significant effect on Employee Performance, which could be seen in the t-calculated value < the t-table (0.129 < 2.011). Career Development (X2) has a positive and significant effect on Employee Performance, it can be concluded that the t-calculated value > t-table (5.438 > 2.011), by simultaneously showing that the Influence of Job Training and Career Development together has a significant effect on Employee Performance (Y) can be concluded by the F-calculated value > F-table (14.493 > 3.20). The result of the determination coefficient of 38.1% of the figure shows that there is an influence of job training and career development variables on employee performance, the remaining 61.9% is influenced by other variables.